The disease burden of Taenia solium cysticercosis in Cameroon. - Nicolas Praet (Public Library of Science (PLoS), 2009)
Background Taenia solium cysticercosis is an important zoonosis in many developing countries. Human neurocysticercosis is recognised as an important cause of epilepsy in regions where the parasite occurs. However, it is largely underreported and there is a lack of data about the disease burden. Because a body of information on human and porcine cysticercosis in Cameroon is becoming available, the present study was undertaken to calculate the impact of this neglected zoonosis. Methods Both the cost and Disability Adjusted Life Year (DALY) estimations were applied. All necessary parameters were collected and imported in R software. Different distributions were used according to the type of information available for each of the parameters. Findings Based on a prevalence of epilepsy of 3.6%, the number of people with neurocysticercosis-associated epilepsy was estimated at 50,326 (95% CR 37,299-65,924), representing 1.0% of the local population, whereas the number of pigs diagnosed with cysticercosis was estimated at 15,961 (95% CR 12,320-20,044), which corresponds to 5.6% of the local pig population. The total annual costs due to T. solium cysticercosis in West Cameroon were estimated at 10,255,202 Euro (95% CR 6,889,048-14,754,044), of which 4.7% were due to losses in pig husbandry and 95.3% to direct and indirect losses caused by human cysticercosis. The monetary burden per case of cysticercosis amounts to 194 Euro (95% CR 147-253). The average number of DALYs lost was 9.0 per thousand persons per year (95% CR 2.8-20.4). Interpretation This study provides an estimation of the costs due to T. solium cysticercosis using country-specific parameters and including the human as well as the animal burden of the zoonotic disease. A comparison with a study in South Africa indicates that the cost of inactivity, influenced by salaries, plays a predominant role in the monetary burden of T. solium cysticercosis. Therefore, knowing the salary levels and the prevalence of the disease might allow a rapid indication of the total cost of T. solium cysticercosis in a country. Ascertaining this finding with additional studies in cysticercosis-endemic countries could eventually allow the estimation of the global disease burden of cysticercosis. The estimated number of DALYs lost due to the disease was higher than estimates already available for some other neglected tropical diseases. The total estimated cost and number of DALYs lost probably underestimate the real values because the estimations have been based on epilepsy as the only symptom of cysticercosis.